Granules
By using pellets composed of ceramic particles and inorganic binders, the problem of difficulty in controlling solar reflectivity and density of existing roof pellets is solved, and the effect of high solar reflectivity and density control is achieved, which is suitable for roof pellets.
Patent Information
- Application Number
- CN202411694399.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2016-05-16
- Filing Date
- 2017-05-11
- Publication Date
- 2025-02-11
AI Technical Summary
The total reflectivity of existing roof pellets is limited by the absorbance of the bedrock, and the absorbance in the binder system is limited by components such as clay, making it difficult to achieve high solar reflectivity and density control.
Particles containing ceramic particles and inorganic binders, wherein the inorganic binders consist of reaction products of alkali metal silicates and hardeners, the ceramic particles represent at least 50% of the total weight, and are prepared by a curing and crushing process. Pellets.
Achieved high solar reflectivity (at least 0.7) and density control, suitable for roof pellets, providing enhanced reflectivity and light weight advantages.
Smart Images

Figure BDA0005151767400000161 
Figure BDA0005151767400000171 
Figure BDA0005151767400000201
Abstract
Description
[0001] This application is a divisional application of the application with application number 2017800300506, application date May 11, 2017, and invention name “Pellets”.
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of U.S. Provisional Patent Applications 62 / 336,988 and 62 / 336,995, both filed on May 16, 2016, the disclosures of which are incorporated herein by reference in their entirety. Background Art
[0004] Conventional roofing granules typically have a core bedrock of dacite, nepheline syenite, rhyolite, andesite, etc., coated with at least one layer of pigmented material. A typical coating consists of sodium silicate and coloring oxide mixed with raw clay. Energy-saving shingles are designed to have improved solar reflectance. Standard white granules colored with titanium dioxide are known, but the total reflectance of these pigments is limited by the absorbance of the bedrock (conventional pigment layers do not completely "hide" the underlying matrix), and the absorbance in the binder system is limited by components such as clay. Summary of the invention
[0005] In one aspect, the present disclosure describes a plurality of pellets comprising ceramic particles bonded together with an inorganic binder comprising at least the reaction product of an alkali metal silicate and a hardener (and in some embodiments, the alkali metal silicate itself), wherein the ceramic particles comprise at least 50%, 55%, 60%, 65%, 70%, 75%, 80%, or even at least 85% by weight of each pellet (in some embodiments, at least 50%, 55%, 60%, 65%, 70%, 75%, 80%, or even at least 85% by weight of each pellet, based on the total weight of the respective pellet. % to 85% by weight, or even in the range of 60% to 85% by weight), wherein each granule has a total porosity in the range of greater than 0% to 50% by volume, 5% to 50% by volume, 20% to 50% by volume, or even 20% to 40% by volume, based on the total volume of the corresponding granule, and wherein the granules have a minimum total solar reflectance (as determined by the Total Solar Reflectance Test described in the Examples) of at least 0.7 (in some embodiments, at least 0.75, or even at least 0.8). In some embodiments, each granule comprises a total of at least 80% by weight (in some embodiments, at least 85%, 90% by weight, or even at least 95% by weight; in some embodiments, in the range of 80% to 95% by weight) of ceramic particles and the reaction product of an alkali metal silicate and a hardener, based on the total weight of the corresponding granule. In some embodiments, each pellet comprises a total of at least 80 wt. % (in some embodiments, at least 85 wt. %, 90 wt. %, or even at least 95 wt. %; in some embodiments, in the range of 80 wt. % to 95 wt. %) ceramic particles, alkali metal silicate, and reaction products of alkali metal silicate and hardener, based on the total weight of the corresponding pellet.
[0006] In this application:
[0007] "Amorphous" refers to a material lacking any long-range crystalline structure as determined by X-ray diffraction techniques as described in the Examples;
[0008] "Ceramics" include amorphous materials, glasses, crystalline ceramics, glass-ceramics, and combinations thereof;
[0009] "Functional additive" means a material that, when present in an amount not greater than 10% by weight of the pellet, substantially changes at least one property of the pellet (e.g., durability and weatherability);
[0010] “Glass” means an amorphous material that exhibits a glass transition temperature;
[0011] "Glass-ceramic" means a ceramic comprising crystals formed by heat treating an amorphous material;
[0012] "Hardener" refers to a material that initiates and / or enhances the hardening of an aqueous silicate solution; hardening implies polycondensation of dissolved silica into a three-dimensional Si-O-Si(Al) bond network and / or crystallization of a new phase; in some embodiments, the pellets contain an excess of hardener.
[0013] "Inorganic" refers to non-organic compounds (broadly, compounds that essentially exclude carbon, hydrogen, and nitrogen);
[0014] "Mineral" means a solid inorganic substance occurring naturally; and
[0015] "Partially crystalline" refers to a material containing components characterized by long range order.
[0016] In another aspect, the present disclosure describes a method of preparing a plurality of pellets described herein, the method comprising:
[0017] curing an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide a cured material; and
[0018] The cured material is crushed to provide pellets. In some embodiments, the curing is at least partially carried out at a temperature in the range of 40°C to 500°C, 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C. In some embodiments, the curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C.
[0019] In another aspect, the present disclosure describes a method of preparing a plurality of pellets described herein, the method comprising:
[0020] mixing materials comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide an agglomerate comprising ceramic particles, an alkali metal silicate precursor, and a hardener; and
[0021] The agglomerates are cured to provide pellets. In some embodiments, curing is at least partially carried out at a temperature in the range of 40°C to 500°C, 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C. In some embodiments, curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C.
[0022] In another aspect, the present disclosure describes a method of preparing a plurality of pellets described herein, the method comprising:
[0023] spray drying an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide an agglomerate comprising ceramic particles, an alkali metal silicate precursor, and a hardener; and
[0024] The agglomerates are cured to provide pellets. In some embodiments, curing is at least partially carried out at a temperature in the range of 40°C to 500°C, 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C. In some embodiments, curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C.
[0025] In another aspect, the present disclosure describes a method of preparing a plurality of pellets described herein, the method comprising:
[0026] providing an aqueous dispersion in a tool comprising a plurality of cavities, the aqueous dispersion comprising ceramic particles, an alkali metal silicate, and a hardener; and
[0027] The aqueous dispersion is cured in a tool to provide pellets. In some embodiments, curing is at least partially carried out at a temperature in the range of 40°C to 500°C, 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C. In some embodiments, curing is carried out in two stages. For example, a first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and a second final curing stage is at least partially at a temperature in the range of 200°C to 500°C.
[0028] Advantages of embodiments of pellets described herein may include enhanced solar reflectance, density control, and size / shape control.
[0029] The granules described herein are useful, for example, as roofing granules. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1A to Figure 1B This is a digital image of an optical microscope of EX2.
[0031] Figure 1C to Figure 1D This is a scanning electron microscope (SEM) digital micrograph of EX2. DETAILED DESCRIPTION
[0032] Suitable alkali metal silicates include cesium silicate, lithium silicate, potassium silicate, or sodium silicate.Exemplary alkali metal silicates are available from commercial sources such as PQ Corporation Malvern, PA.
[0033] Exemplary hardeners include aluminum phosphate, aluminosilicate (e.g., amorphous aluminosilicate), fluorosilicate, Portland cement, cryolite, calcium salts (e.g., CaCl2) and calcium silicate. In some embodiments, the hardener is at least one of aluminum phosphate, amorphous aluminosilicate, fluorosilicate, Portland cement or calcium silicate. In some embodiments, the hardener is amorphous. In some embodiments, the hardener includes amorphous aluminosilicate. Exemplary hardeners are available from commercial sources, such as Budenheim, Inc., Budenheim, Germany and Solvay Fluorides, LLC, Houston, TX.
[0034] In some embodiments, the inorganic binder comprises at least 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, or 45%, or even up to 50% by weight (in some embodiments, in the range of 5% to 50%, 10% to 50%, or even 25% to 50% by weight) of each pellet, based on the total weight of the corresponding pellet. In some embodiments, the ratio of alkali metal silicate to hardener is in the range of 20:1 to 2:1.
[0035] In some embodiments, the ceramic particles include at least one component having a total solar reflectance of at least 0.75, or even at least 0.8 (as measured by the total solar reflectance test described in the examples). Such exemplary ceramic particles include aluminum hydroxide (calcined and uncalcined), metal or metalloid oxides (e.g., silica (e.g., cristobalite, quartz, etc.), aluminates (e.g., alumina, mullite, etc.), titanates (e.g., titanium dioxide) and zirconium oxide), silicate glasses (e.g., soda-lime-silica glass, borosilicate glass), porcelain or marble. In some embodiments, the ceramic particles include minerals. Exemplary ceramic particles can be prepared by techniques known in the art and / or obtained from commercial sources such as Vanderbilt Minerals, LLC, Norwalk, CT, Connecticut; DADCO, Lausanne, Switzerland; and American Talc Company, Allamoore, TX, Texas.
[0036] In some embodiments, the ceramic particles of each pellet contain no more than 10 wt% (in some embodiments, no more than 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt%, or even 0 wt%) TiO2 on a theoretical oxide basis, based on the total weight of the pellets of the corresponding pellets. In some embodiments, the ceramic particles of each pellet contain no more than 10 wt% (in some embodiments, no more than 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt%, or even 0 wt%) pure TiO2, based on the total weight of the pellets of the corresponding pellets. In some embodiments, the ceramic particles of each pellet contain no more than 10 wt% (in some embodiments, no more than 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt%, or even 0 wt%) pure Al2O3, based on the total weight of the pellets of the corresponding pellets.
[0037] In some embodiments, the ceramic particles have an average particle size in the range of 200 nm to 200 μm, 200 nm to 100 μm, 250 nm to 50 μm, 500 nm to 2 μm, 2 μm to 5 μm, or even 5 μm to 20 μm. In some embodiments, the ceramic particles have a bimodal distribution of sizes.
[0038] In some embodiments, the ceramic particles each have a longest dimension, wherein the pellets each have a longest dimension, and wherein the longest dimension of each ceramic particle of a given pellet is no greater than 20% (in some embodiments, no greater than 25%) of the diameter of the given pellet.
[0039] In some embodiments, the pellets further comprise at least one of a functional additive (e.g., a rheology modifier, a durability modifier, and a flux), an organic binder, or a pigment. Exemplary rheology modifiers include surfactants. Exemplary durability modifiers include nanosilica, pyrogenic ("fumed") silica, and silica fume, which are available from, for example, Evonik Industries, Essen, Germany.
[0040] Exemplary fluxing agents include borax, available from, for example, Rio Tinto Minerals, Boron, CA. Exemplary organic binders include dextrin and carboxymethyl cellulose, available from, for example, Dow Chemical Company, Midland, MI.
[0041] Embodiments of the pellets described herein can be prepared by a variety of methods. For example, one method includes:
[0042] curing an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide a cured material; and
[0043] The solidified material is crushed to provide pellets.
[0044] The dispersion can be prepared using techniques known in the art. In some embodiments, water is present in the aqueous dispersion at up to 75 wt % (in some embodiments, up to 70 wt %, 65 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %, or even up to 15 wt % (in some embodiments; in the range of 15 wt % to 75 wt %, 15 wt % to 50 wt %, or even 15 wt % to 35 wt %) based on the total weight of the aqueous dispersion.
[0045] The aqueous dispersion can be cured by techniques known in the art, including heating the dispersion in an oven. In some embodiments, curing is at least partially carried out at a temperature in the range of 40°C to 500°C, 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C. In some embodiments, curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C. In some embodiments, the heating rate of each stage is one or more rates in the range of 5°C / min to 50°C / min. The selection of one or more heating rates and one or more temperatures may be affected by the composition and / or size of the curing material.
[0046] Techniques for crushing and screening the solidified material to provide the desired pellet size and particle size distribution are known in the art.
[0047] The second method includes:
[0048] A material comprising ceramic particles, an alkali metal silicate precursor and a hardener is mixed to provide
[0049] an agglomerate comprising ceramic particles, an alkali metal silicate precursor, and a hardener; and
[0050] The agglomerates are solidified to provide pellets.
[0051] The materials may be mixed to agglomerate the materials using techniques known in the art. Typically, a liquid such as water is introduced (periodically or continuously) to help agglomerate the materials.
[0052] In some embodiments, the material is an aqueous dispersion, which can be prepared using techniques known in the art. In some embodiments, water is present at up to 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, or even up to 15% by weight (in some embodiments; in the range of 15% to 75%, 15% to 50%, or even 15% to 35% by weight), based on the total weight of the aqueous dispersion.
[0053] Can be cured by technology known in the art, including heating the material to be cured in an oven. In some embodiments, curing is at least partially carried out at a temperature within the range of 40°C to 500°C, 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C. In some embodiments, curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature within the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature within the range of 200°C to 500°C. In some embodiments, the heating rate of each stage is one or more rates within the range of 5°C / min to 50°C / min. The selection of one or more heating rates and one or more temperatures may be affected by the composition and / or size of the curing material.
[0054] The third method includes:
[0055] spray drying an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide an agglomerate comprising ceramic particles, an alkali metal silicate precursor, and a hardener; and
[0056] The agglomerates are solidified to provide pellets.
[0057] The dispersion can be prepared using techniques known in the art. In some embodiments, water is present in the aqueous dispersion at up to 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, or even up to 15% by weight (in some embodiments, in the range of 15% to 75%, 15% to 50%, or even 15% to 35% by weight), based on the total weight of the aqueous dispersion.
[0058] Agglomerates can be cured by techniques known in the art, including curing in a batch oven or a continuous rotary furnace. In some embodiments, curing is at least partially carried out at a temperature in the range of 40°C to 500°C, 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C. In some embodiments, curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C. In some embodiments, the heating rate of each stage is one or more rates in the range of 5°C / min to 50°C / min. The selection of one or more heating rates and one or more temperatures may be affected by the composition and / or size of the curing material.
[0059] The fourth method includes:
[0060] providing an aqueous dispersion in a tool comprising a plurality of cavities, the aqueous dispersion comprising ceramic particles, an alkali metal silicate, and a hardener; and
[0061] The aqueous dispersion is solidified in a tool to provide pellets.
[0062] The dispersion can be prepared using techniques known in the art. In some embodiments, water is present in the aqueous dispersion at up to 75%, 70%, 65%, 60%, 55%, 50%, 45%, 40%, 35%, 30%, 25%, 20%, or even up to 15% by weight (in some embodiments; in the range of 15% to 75%, 15% to 50%, or even 15% to 35% by weight), based on the total weight of the aqueous dispersion.
[0063] The tool can be a mold with at least one mold cavity, more generally a plurality of cavities. The cavity can be configured to have a desired three-dimensional shape. In an exemplary embodiment, the shape of the cavity can be described as a triangle observed from the top. Other exemplary cavity shapes include circular, rectangular, square, hexagonal, star-shaped, etc., to provide shapes such as cubes, truncated cubes, pyramids, truncated pyramids, triangles, tetrahedrons, spheres, hemispheres, cones, and combinations thereof. These shapes generally have substantially uniform depth dimensions. Such molds can be prepared using techniques known in the art, including those reported in U.S. Patent 8,142,531 (Adefris et al.), the disclosure of which is incorporated herein by reference.
[0064] Can use the technology known in the art to cure, including heating tool and dispersion in the cavity in an oven.In some embodiments, curing is at least partially carried out at a temperature in the range of 40 ℃ to 500 ℃, 50 ℃ to 450 ℃, 50 ℃ to 350 ℃, 50 ℃ to 250 ℃, 50 ℃ to 200 ℃, 50 ℃ to 150 ℃, 50 ℃ to 100 ℃, or even 50 ℃ to 80 ℃.In some embodiments, curing is carried out in two stages.For example, the first curing stage is at least partially at a temperature in the range of 20 ℃ to 100 ℃, and the second final curing stage is at least partially at a temperature in the range of 200 ℃ to 500 ℃.In some embodiments, the heating rate of each stage is one or more rates in the range of 5 ℃ / min to 50 ℃ / min.The selection of one or more heating rates and one or more temperatures may be affected by the composition and / or size of the curing material.
[0065] In some embodiments, the pellets have a particle size ranging from 25 microns to 5 millimeters, 50 microns to 1 millimeter, 100 microns to 500 microns, 200 microns to 500 microns; 500 microns to 2 millimeters; or even 2 millimeters to 5 millimeters.
[0066] In some embodiments, the inorganic binder is amorphous. In some embodiments, the inorganic binder is partially crystalline.
[0067] In some embodiments, the pellets have a particle size of 0.5 g / cm 3 Up to 3.0g / cm 3 Density within the range.
[0068] In some embodiments, the pellets have an outer surface when cured (ie, the pellets have a manufactured surface, rather than pellets obtained by crushing).
[0069] The pellets can be any of a variety of shapes, including cubes, truncated cubes, pyramids, truncated pyramids, triangles, tetrahedrons, spheres, hemispheres, and cones. In some embodiments, the pellets can have a first face and a second face separated by a thickness. In some embodiments, such pellets also include at least one of a straight wall or an inclined wall.
[0070] In some embodiments, the pellets described herein have a Rolling Toughness Value of at least 70, 75, 80, 85, 90, 95, 96, 97, 98, or even at least 99 prior to immersion in water or at least 50, 55, 60, 65, 70, 75, 80, 85, or even at least 90 after immersion in water at 20°C ± 2°C for 2 months (as determined by the Rolling Toughness Value Test described in the Examples).
[0071] In some embodiments, the pellets have a Stain Value (as determined by the Stain Value Test described in the Examples) of no greater than 15 (in some embodiments, no greater than 10, 5, 4, 3, 2, 1, or even no greater than 0.1).
[0072] The granules described herein can be used, for example, as roofing granules. For example, the granules described herein can be used to prepare a roofing material comprising a substrate and the granules thereon. In some embodiments, the roofing material has a total solar reflectance of at least 0.7.
[0073] Advantages of embodiments of the granules described herein may include enhanced solar reflectance and light weight compared to standard roofing granules.
[0074] Exemplary embodiments
[0075] 1A. A plurality of pellets comprising ceramic particles bonded together with an inorganic binder comprising the reaction product of at least an alkali metal silicate and a hardener (and in some embodiments, the alkali metal silicate itself), wherein the ceramic particles comprise at least 50% by weight of each pellet, based on the total weight of the respective pellet
[0076] (In some embodiments, at least 55%, 60%, 65%, 70%, 75%, 80%, or even at least 85% by weight; in some embodiments, between 50% and 85%, or even between 60% and 85% by weight.
[0077] %, wherein each pellet has a total porosity in the range of greater than 0 volume % to 50 volume % (in some embodiments, in the range of 5 volume % to 50 volume %, 20 volume % to 50 volume %, or even 20 volume % to 40 volume %) based on the total volume of the corresponding pellet, and wherein the pellets have a minimum total solar reflectance of at least 0.7 (in some embodiments, at least 0.75, or even at least 0.8).
[0078] 2A. A plurality of pellets according to exemplary embodiment 1A, wherein the respective pellets
[0079] Each pellet comprises a total of at least 80 wt. % (in some embodiments, at least 85 wt. %, 90 wt. % or even at least 95 wt. %; in some embodiments, in the range of 80 wt. % to 95 wt. %) of the ceramic particles and the reaction product of the alkali metal silicate and the hardener, based on the total weight of the pellet.
[0080] 3A. A plurality of pellets according to exemplary embodiment 1A, wherein the respective pellets
[0081] Each pellet comprises a total of at least 80 wt. % (in some embodiments, at least 85 wt. %, 90 wt. %, or even at least 95 wt. %; in some embodiments, in the range of 80 wt. % to 95 wt. %) of the ceramic particles, the alkali metal silicate, and the reaction product of the alkali metal silicate and the hardener, based on the total weight of the pellet.
[0082] 4A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0083] The ceramic particles each have a longest dimension, wherein the pellets each have a longest dimension, and wherein the longest dimension of each ceramic particle of a given pellet is no greater than 20% (in some embodiments, no greater than 25%) of the diameter of the given pellet.
[0084] 5A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein based on
[0085] The ceramic particles of each pellet contain no more than 10 wt. % (in some embodiments, no more than 5 wt. %, 4 wt. %, 3 wt. %, 2 wt. %, 1 wt. % or even 0 wt. %) pure TiO2, based on the total weight of the pellet of the respective pellet.
[0086] 6A. A plurality of pellets according to any one of exemplary embodiments 1A to 4A, wherein the base
[0087] The ceramic particles of each pellet contain no more than 10 wt. % (in some embodiments, no more than 5 wt. %, 4 wt. %, 3 wt. %, 2 wt. %, 1 wt. % or even 0 wt. %) TiO2 on a theoretical oxide basis, based on the total weight of the pellets of the respective pellets.
[0088] 7A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein based on
[0089] The ceramic particles of each pellet contain no more than 10 wt. % (in some embodiments, no more than 5 wt. %, 4 wt. %, 3 wt. %, 2 wt. %, 1 wt. % or even 0 wt. %) pure Al2O3, based on the total weight of the pellets of the respective pellets.
[0090] 8A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0091] The pellets have a gloss of at least 70 (in some embodiments, at least 75, 80, 85, 90, 95, 96, 97, 98, or even at least 99) before immersion in water and after immersion at 20°C.
[0092] ±2°C for two months after at least 50 (in some embodiments, at least 55,
[0093] 60, 65, 70, 75, 80, 85 or even at least 90).
[0094] 9A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein based on
[0095] The inorganic binder comprises at least 5 wt % (in some embodiments, at least 10 wt %, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, or 45 wt %, or even up to 50 wt % of each pellet; in some embodiments, between 5 wt % and 50 wt %, between 10 wt % and 50 wt %, or even between 25 wt % and 50 wt % of each pellet, based on the total weight of the respective pellet.
[0096] range).
[0097] 10A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0098] The pellets have a particle size ranging from 25 microns to 5 millimeters (in some embodiments, 50 microns to 1 millimeter, 100 microns to 500 microns, 200 microns to 500 microns; 500 microns to 2 millimeters; or even 2 millimeters to 5 millimeters).
[0099] 11A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0100] The ceramic particles have an average particle size in the range of 200 nanometers to 200 micrometers (in some embodiments, 200 nanometers to 100 micrometers, 250 nanometers to 50 micrometers, 500 nanometers to 2 micrometers, 2 micrometers to 5 micrometers, or even 5 micrometers to 20 micrometers).
[0101] 12A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0102] The ceramic particles have a bimodal distribution of sizes.
[0103] 13A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0104] Inorganic binders are amorphous.
[0105] 14A. A plurality of pellets according to any one of exemplary embodiments 1A to 11A, wherein
[0106] The inorganic binder is partially crystalline.
[0107] 15A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0108] The alkali metal silicate is at least one of cesium silicate, lithium silicate, potassium silicate or sodium silicate.
[0109] 16A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0110] The hardener is amorphous.
[0111] 17A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0112] The hardener is at least one of aluminum phosphate, amorphous aluminosilicate, fluorosilicate, Portland cement or calcium silicate.
[0113] 18A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0114] The hardener is at least one of aluminum phosphate, aluminosilicate, fluorosilicate, Portland cement, cryolite, a calcium salt (eg, CaCl2), or calcium silicate.
[0115] 19A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0116] The ceramic particles include at least one component having a total solar reflectance of at least 0.7 (as measured by the Total Solar Reflectance Test described in the Examples). Such exemplary ceramic particles include aluminum hydroxide, metal or metalloid oxides (e.g., silica (e.g., cristobalite, quartz, etc.), aluminates (e.g., alumina, mullite, etc.), titanates (e.g., titanium dioxide), and zirconium oxide), silicate glass (e.g., soda-lime-silica glass, borosilicate glass), porcelain, or marble.
[0117] 20A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0118] The ceramic particles include minerals.
[0119] 21A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0120] The pellets also include at least one of a functional additive (eg, a rheology modifier (eg, a surfactant), a durability modifier (eg, nano-silica), and a flux), an organic binder, or a pigment.
[0121] 22A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein each
[0122] The corresponding pellets have a 3 Up to 3.0g / cm 3 Density within the range.
[0123] 23A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0124] The pellets have an outer surface when cured.
[0125] 24A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0126] The pellets are in the shape of at least one of a cube, a truncated cube, a pyramid, a truncated pyramid, a triangle, a tetrahedron, a sphere, a hemisphere, or a cone.
[0127] 25A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein each
[0128] The pellet has a first side and a second side separated by a thickness.
[0129] 26A. A plurality of pellets according to exemplary embodiment 23A, wherein at least some of the pellets further
[0130] Includes at least one of a straight wall or an inclined wall.
[0131] 27A. A plurality of pellets according to any one of the preceding A exemplary embodiments, wherein the
[0132] The pellets have no more than 15 (in some embodiments, no more than 10, 5, 4, 3,
[0133] 2, 1 or even not more than 0.5).
[0134] 28A. A roof comprising any one of the above A exemplary embodiments
[0135] Multiple pellets.
[0136] 29A. A roofing material comprising a substrate and the granules of any of Exemplary Embodiments 1A to 27A (in some embodiments, the roofing material has a total solar reflectance of at least 0.7).
[0137] 1B. A method for preparing a plurality of particles according to any one of exemplary embodiments 1A to 27A
[0138] A method for preparing a material, the method comprising:
[0139] curing an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide a cured material; and
[0140] The solidified material is crushed to provide the pellets.
[0141] 2B. The method according to exemplary embodiment 1B, wherein the curing is at least partially
[0142] At a temperature in the range of 40°C to 500°C (in some embodiments, in the range of 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C). In some embodiments, curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C. In some embodiments, the heating rate for each stage is one or more rates in the range of 5°C / min to 50°C / min.
[0143] 3B. A method according to any one of the aforementioned B exemplary embodiments, wherein based on the
[0144] The water may be present in an amount up to 75 wt % (in some embodiments, up to 70 wt %, 65 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %) based on the total weight of the aqueous dispersion.
[0145] or even up to 15 wt %; in some embodiments, in the range of 15 wt % to 75 wt %, 15 wt % to 50 wt %, or even 15 wt % to 35 wt %) is present in the aqueous dispersion.
[0146] 1C. A method for preparing a plurality of particles according to any one of exemplary embodiments 1A to 27A
[0147] A method for preparing a material, the method comprising:
[0148] mixing materials comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide agglomerates comprising ceramic particles, an alkali metal silicate precursor, and a hardener; and curing the agglomerates to provide the granules.
[0149] 2C. The method of example embodiment 1C, wherein the material is an aqueous dispersion.
[0151] 3C. A method according to any one of the preceding C exemplary embodiments, wherein during the mixing period
[0152] Water was added to the material from time to time.
[0153] 4C. A method according to any one of the preceding C exemplary embodiments, wherein the curing
[0154] At least partially at a temperature in the range of 40°C to 500°C (in some embodiments, in the range of 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C). In some embodiments, curing is performed in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C. In some embodiments, the heating rate for each stage is one or more rates in the range of 5°C / min to 50°C / min.
[0155] 5C. A method according to any one of the preceding C exemplary embodiments, wherein based on the
[0156] The water may be present in an amount up to 75 wt % (in some embodiments, up to 70 wt %, 65 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %) based on the total weight of the aqueous dispersion.
[0157] or even up to 15 wt %; in some embodiments, within the range of 15 wt % to 75 wt %, 15 wt % to 50 wt %, or even 15 wt % to 35 wt %).
[0158] 1D. A method for preparing a plurality of particles according to any one of exemplary embodiments 1A to 27A
[0159] A method for preparing a material, the method comprising:
[0160] Spray drying an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide an agglomerated product comprising ceramic particles, an alkali metal silicate precursor, and a hardener.
[0161] things; and
[0162] The agglomerates are solidified to provide the pellets.
[0163] 2D. A method according to exemplary embodiment 1D, wherein the curing is at least partially
[0164] At a temperature in the range of 40°C to 500°C (in some embodiments, in the range of 50°C to 450°C, 50°C to 350°C, 50°C to 250°C, 50°C to 200°C, 50°C to 150°C, 50°C to 100°C, or even 50°C to 80°C). In some embodiments, curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C. In some embodiments, the heating rate for each stage is one or more rates in the range of 5°C / min to 50°C / min.
[0165] 3D. A method according to any one of the preceding D exemplary embodiments, wherein based on the
[0166] The water may be present in an amount up to 75 wt % (in some embodiments, up to 70 wt %, 65 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %) based on the total weight of the aqueous dispersion.
[0167] or even up to 15 wt %; in some embodiments, in the range of 15 wt % to 75 wt %, 15 wt % to 50 wt %, or even 15 wt % to 35 wt %) is present in the aqueous dispersion.
[0168] 1E. A method for preparing a plurality of particles according to any one of exemplary embodiments 1A to 27A
[0169] A method for preparing a material, the method comprising:
[0170] providing an aqueous dispersion in a tool comprising a plurality of cavities, the aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener; and
[0171] The aqueous dispersion is solidified in a tool to provide the pellets.
[0172] 2E. A method according to exemplary embodiment 1E, wherein the curing is at least partially
[0173] In the range of 40°C to 500°C (in some embodiments, in the range of 50°C to 450°C,
[0174] 50℃ to 350℃、50℃ to 250℃、50℃ to 200℃、50℃ to 150℃、
[0175] In some embodiments, the curing is carried out at a temperature in the range of 50°C to 100°C, or even in the range of 50°C to 80°C. In some embodiments, the curing is carried out in two stages. For example, the first curing stage is at least partially at a temperature in the range of 20°C to 100°C, and the second final curing stage is at least partially at a temperature in the range of 200°C to 500°C. In some embodiments, the heating rate for each stage is one or more rates in the range of 5°C / min to 50°C / min.
[0176] 3E. The method according to any of the preceding E exemplary embodiments, wherein the water is present at up to 75 wt % (in some embodiments, up to 70 wt %, 65 wt %, 60 wt %, 55 wt %, 50 wt %, 45 wt %, 40 wt %, 35 wt %, 30 wt %, 25 wt %, 20 wt %) based on the total weight of the aqueous dispersion.
[0177] or even up to 15 wt %; in some embodiments, in the range of 15 wt % to 75 wt %, 15 wt % to 50 wt %, or even 15 wt % to 35 wt %) is present in the aqueous dispersion.
[0178] The following examples further illustrate the advantages and embodiments of the present invention, but the specific materials and amounts thereof mentioned in these examples, as well as other conditions and details, should not be construed as unduly limiting the present invention. Unless otherwise indicated, all parts and percentages are by weight.
[0179] Material
[0180] Table 1
[0181]
[0182]
[0183] method
[0184] General Method I for Preparing Pellets
[0185] The pellets were generally prepared as follows, further details of which are provided in the Examples below: First, the structural filler ("VANSIL W50"), the color enhancer ("ATH SH20") were homogenized by ball milling. Next, the hardener was added to the liquid silicate and stirred vigorously for 10 minutes. The homogenized dry portion was combined with the liquid portion and stirred at 1000 rpm for 15 minutes. The slurry was cast into a triangular mold cavity with a depth of 0.42 mm and each side of 1.693 mm with a draft angle of 98 degrees. The cast pellets were subjected to a two-stage cure.
[0186] General Method for Preparing Pellets II
[0187] The pellets were formed in a drum agglomerator (Eirich mixer, obtained from Maschinenfabrik Gustav Eirich GmbH & Co., Hardheim, Germany). The liquid portion comprising liquid sodium silicate and a color enhancer ("ATH SH 20") were co-milled with a hardener and wollastonite. The resulting green pellets were cured as described in "General Method I for Preparing Granules". After curing, the pellets were sieved and the fraction of 600 to 1000 microns was retained.
[0188] General Method for Preparing Pellets III
[0189] The pellets were generally prepared as follows, further details of which are provided in the Examples below: First, the structural filler ("CaCO3 #10") and the color enhancer ("OPIWHITE") were mixed together. Next, the hardener ("OPTIPOZZ") was combined with the liquid silicate ("STAR") and additional water and stirred vigorously for 10 minutes. The homogenized dry portion was combined with the liquid portion and stirred at 1000 rpm for 15 minutes. The slurry was cast into trays and crushed into pellets (EX4) after the first stage of curing. For EX4, the 425 micron to 2000 micron fraction was screened and used for further second stage curing and evaluation. All pellets were subjected to two stage curing.
[0190] Method for determining reflectivity
[0191] The reflectance of the examples was tested using a spectroscopic reflectometer (obtained as Model SSR-ER v6 from Devices and Services Co., Dallas, TX) using a 1.5E air mass setting. For the "cup" measurement, the pellets were loaded into a sample holder with a depth of approximately 5 mm. The surface of the pellets was smoothed using a roller.
[0192] Method for determining the rolling toughness of granular materials
[0193] Granule rolling toughness values (weight %) were determined before and after immersion in water for 2 months using the Abrasion Resistance Test Roofing Procedure from the Asphalt Roofing Manufacturers Association (ARMA) Granule Test Procedures Manual, ARMA Form No. 441-REG-96 (the disclosure of which is incorporated herein by reference). More specifically, 125 grams of the sample were placed on a screen shaker (obtained under the trade designation "RX-29RO-TAP" (WS Tyler Industrial Group, Mentor, OH)) and agitated for 10 minutes to ensure complete removal of material finer than the original diameter (100 mesh) corresponding to the smallest fraction of the granule distribution. 100 grams of the granules were weighed and placed in a 5.1 cm (2 inch) diameter pipe tester. The tube was rotated by rotating the end of the tube 100 times, controlling the rotation rate so that the pellets fell cleanly without sliding. At the end of the test, the top cap was unscrewed, the tube was turned over, the contents were poured into a sieve, and the dish was placed in a sieve shaker ("RO-TAP") and run for 5 minutes.
[0194] The rolling toughness values before and after immersion in water at 20°C ± 2°C are reported as the weight percentage of the material remaining on the sieve having a mesh (100 mesh) corresponding to the original diameter of the smallest fraction of the particle distribution.
[0195] Methods for stain resistance testing
[0196] The four-day stain test is an accelerated measure of the propensity of roofing pellets to absorb asphalt oil in an asphalt-based substrate and was conducted according to the procedure described in PCT Publication WO 2010 / 091326 A2, published on August 12, 2010, the disclosure of which is incorporated herein by reference. More specifically, pellets from each sample were partially embedded in asphalt that had been heated to 180° C. The partially embedded pellets were placed on a tray in an oven at 80° C. for 96 hours (4 days). The tray was removed from the oven and the asphalt was allowed to cool to room temperature.
[0197] The staining of the pellets on the asphalt substrate was then measured under a colorimeter (obtained from HunterLab, Reston, VA under the trade designation "LABSCAN") and the staining value was calculated. Staining was measured by the total color change ΔE measured in CIELAB (L*a*b*) units for the unexposed and 4-day heat-exposed pellets. Staining value = ΔE* = [(L*4 days - L*0 days) 2 +(a*4 days - a*0 days) 2 +(b*4 days - b*0 days)2] 1 / 2 Higher stain values represent greater undesirable color changes.
[0198] Method for determining crystallinity
[0199] The X-ray diffractometer (obtained from Rigaku Americas, The Woodlands, TX under the trade designation “RIGAKU MINI FLEXII”) was used to irradiate the samples with CuKα radiation. The crystal structure and phase transitions were investigated by powder X-ray diffraction (XRD) in the 2θ range from 20 to 80.
[0200] Methods for determining porosity
[0201] Brunauer, Emmett, and Teller (BET) surface areas and total pore volumes were determined by N2 adsorption. More specifically, the samples were characterized by N2 adsorption at 77°K using a gas adsorption analyzer (obtained under the trade designation "MICROMERITICS"; Model ASAP-2020 from Micromeritics Instruments, Norcross, GA). Each sample was degassed at 573°K for 24 hours to remove any moisture or adsorbed contaminants that may be present on the surface. The average pore size D p By D p =4V t / S calculation, where V t is the total volume of the pores, and S is the BET surface area.
[0202] Examples 1 to 4 (EX1 to EX4) and Comparative Example A (CE-A)
[0203] EX1 and EX2 were prepared as described in "General Method I for Preparing Pellets". EX3 was prepared as described in "General Method II for Preparing Pellets". EX4 was prepared as described in "General Method III for Preparing Pellets". The composition and processing parameters of each of EX1 to EX4 are summarized in Table 2 below.
[0204] Table 2
[0205]
[0206] CE-A is a commercial roofing granule available from 3M Company, St. Paul, MN under the trade designation "3M CLASSIC ROOFING GRANULES W9300".
[0207] Figure 1A to Figure 1B This is a digital image of an optical microscope of EX2, and Figure 1C Figure 1D is a digital scanning electron microscope (SEM) image of EX2.
[0208] EX1 to EX4 were characterized using the above-described method for determining reflectivity, method for determining pellet rolling toughness, method for stain resistance testing, powder X-ray diffraction, and Brunauer, Emmett, and Teller (BET) method. The results are summarized in Table 3 below.
[0209] Table 3
[0210]
[0211] The X-ray diffraction (XRD) pattern (not shown) showed no new crystalline phases in the final product and only phases corresponding to components of engineered fillers and pigments were recorded. The amorphous hump located between 20 and 40 degrees 2θ indicated the disordered structure of the siliceous bonding network.
[0212] Without departing from the scope and spirit of the present disclosure, foreseeable variations and modifications of the present disclosure will be apparent to those skilled in the art.The present invention should not be limited to the embodiments shown in this application for illustrative purposes.
Claims
1. A plurality of pellets comprising ceramic particles bonded together with an inorganic binder comprising the reaction product of at least an alkali metal silicate and a hardener, wherein the ceramic particles comprise at least 50 weight percent of each pellet based on the total weight of the respective pellet, wherein each pellet has a total porosity in the range of greater than 20 volume percent to 50 volume percent based on the total volume of the respective pellet, and wherein the pellets have a minimum total solar reflectance of at least 0.70, wherein the pellets are formed by two stage curing, a first curing stage at least partially at a temperature in the range of 20°C to 100°C, and a second final curing stage at least partially at a temperature in the range of 200°C to 500°C.
2. The plurality of granules of claim 1, wherein the granules have a minimum total solar reflectance of at least 0.
75.
3. A plurality of pellets according to any one of the preceding claims, wherein the pellets have a minimum total solar reflectance of at least 0.
80.
4. The plurality of pellets of claim 1 or 2, wherein each pellet comprises a total of at least 80 wt. % of the ceramic particles and the reaction product of the alkali metal silicate and the hardener, based on the total weight of the respective pellet.
5. The plurality of pellets of claim 1 or 2, wherein the ceramic particles each have a longest dimension, wherein the pellets each have a longest dimension, and wherein the longest dimension of each ceramic particle of a given pellet is no greater than 20% of the diameter of the given pellet.
6. The plurality of pellets of claim 1 or 2, wherein the ceramic particles of each pellet comprise no more than 10 wt. % TiO2 on a theoretical oxide basis, based on the total weight of the pellets of the respective pellets.
7. The plurality of pellets of claim 1 or 2, wherein the ceramic particles of each pellet comprise no more than 10 wt. % pure TiO2, based on the total weight of the pellets of the respective pellets.
8. The plurality of pellets of claim 1 or 2, wherein the ceramic particles of each pellet comprise no more than 10 wt. % pure Al2O3, based on the total weight of the pellets of the respective pellets.
9. The plurality of pellets of claim 1 or 2, wherein the pellets have a rolling toughness value of at least 70.
10. The plurality of pellets of claim 1 or 2, wherein the pellets have a rolling toughness value of at least 35 after being immersed in water at 20°C ± 2°C for 2 months.
11. The plurality of pellets according to claim 1 or 2, wherein the inorganic binder comprises at least 5 weight percent of each pellet, based on the total weight of the respective pellet.
12. The plurality of pellets of claim 1 or 2, wherein the pellets have a particle size in the range of 25 microns to 5 millimeters.
13. The plurality of pellets of claim 1 or 2, wherein the ceramic particles have an average particle size in a range of 200 nanometers to 200 micrometers.
14. The plurality of pellets of claim 1 or 2, wherein the inorganic binder is amorphous.
15. The plurality of pellets of claim 1 or 2, wherein the inorganic binder is partially crystalline.
16. The plurality of pellets of claim 1 or 2, wherein the alkali metal silicate is at least one of cesium silicate, lithium silicate, potassium silicate, or sodium silicate.
17. The plurality of pellets of claim 1 or 2, wherein the hardener is amorphous.
18. The plurality of pellets of claim 1 or 2, wherein the hardener is at least one of aluminum phosphate, amorphous aluminosilicate, fluorosilicate, Portland cement, or calcium silicate.
19. The plurality of pellets of claim 1 or 2, wherein the hardener is at least one of aluminum phosphate, aluminosilicate, fluorosilicate, Portland cement, cryolite, a calcium salt, or calcium silicate.
20. The plurality of pellets of claim 1 or 2, wherein the ceramic particles comprise at least one of aluminum hydroxide, metal oxides, metalloid oxides, soda-lime-silica glass, borosilicate glass, porcelain, or marble.
21. The plurality of pellets of claim 1 or 2, wherein the ceramic particles comprise a mineral.
22. The plurality of pellets of claim 1 or 2, wherein the pellets further comprise at least one of a functional additive, an organic binder, or a pigment.
23. The plurality of pellets of claim 1 or 2, wherein the pellets have a stain value of no greater than 15.
24. A roofing material comprising a substrate and the granules of claim 1 or 2, wherein the roofing material has a total solar reflectance of at least 0.
7.
25. A method for preparing a plurality of pellets according to claim 1 or 2, the method comprising one of the following steps: curing an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide a cured material; and The solidified material is crushed to provide the pellets.
26. A method of preparing a plurality of pellets according to claim 1 or 2, the method comprising: mixing materials comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide an agglomerate comprising ceramic particles, an alkali metal silicate precursor, and a hardener; as well as The agglomerates are solidified to provide the pellets.
27. A method of preparing a plurality of pellets according to claim 1 or 2, the method comprising: spray drying an aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener to provide an agglomerate comprising ceramic particles, an alkali metal silicate precursor, and a hardener; as well as The agglomerates are solidified to provide the pellets.
28. A method of preparing a plurality of pellets according to claim 1 or 2, the method comprising: providing an aqueous dispersion in a tool comprising a plurality of cavities, the aqueous dispersion comprising ceramic particles, an alkali metal silicate precursor, and a hardener; as well as The aqueous dispersion is solidified in a tool to provide the pellets.
Citation Information
Patent Citations
Shaped abrasive particles with a sloping sidewall
US8142531B2
Dust suppressants
WO2010091326A2